2016
DOI: 10.1016/j.commatsci.2016.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen vacancy diffusion in bulk SrTiO3 from density functional theory calculations

Abstract: Point defects and their diffusion contribute significantly to the properties of perovskite materials. However, even for the prototypical case of oxygen vacancies in SrTiO 3 (STO), the predictions of oxygen vacancy activity vary widely. Here we present a comprehensive and systematic study of the diffusion barriers for this material. We use density functional theory (DFT) and assess the role of different supercell sizes, density functionals, and charge states. Our results show that vacancy-induced octahedral rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
57
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 42 publications
9
57
1
Order By: Relevance
“…These results appear to be in agreement with the scarce experimental data that is available for compressive biaxial strains 37 but in apparent disagreement with previous DFT results reported by Al-Hamadany et al 38 . The reasons for the disagreements between our theoretical NEB estimations and analogous computational results previously reported 38 could be the use of different exchange-correlation energy functionals and simulation supercells, which are known to affect the description of polar and antiferrodistortive oxygen octahedral distortions in functional oxide perovskites 47 , 79 . In order to fully test the reliability of our zero-temperature NEB results, we performed complementary ab initio molecular dynamics (AIMD) simulations in which lattice thermal excitations are fully taken into account and no particular diffusion path needs to be guessed 59 .…”
Section: Resultscontrasting
confidence: 53%
See 2 more Smart Citations
“…These results appear to be in agreement with the scarce experimental data that is available for compressive biaxial strains 37 but in apparent disagreement with previous DFT results reported by Al-Hamadany et al 38 . The reasons for the disagreements between our theoretical NEB estimations and analogous computational results previously reported 38 could be the use of different exchange-correlation energy functionals and simulation supercells, which are known to affect the description of polar and antiferrodistortive oxygen octahedral distortions in functional oxide perovskites 47 , 79 . In order to fully test the reliability of our zero-temperature NEB results, we performed complementary ab initio molecular dynamics (AIMD) simulations in which lattice thermal excitations are fully taken into account and no particular diffusion path needs to be guessed 59 .…”
Section: Resultscontrasting
confidence: 53%
“…For integrations within the Brillouin zone (BZ), we used a -centered -point grid of for the 20-atoms simulation cell and scaled it conveniently to maintain an equivalent -point density for the rest of cases. All oxygen vacancies were assumed to be neutrally charged and non-magnetic ( ) as in previous DFT studies this configuration has been shown to render the lowest energy for bulk off-stoichiometric 9 , 47 , 48 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…V O formation energies of BTO, [55,56] LAO, [57,58] and STO [59][60][61][62][63][64] are much greater than that of LNO. Therefore, one would expect that the V O would form preferentially in the underlying LNO layer rather than in the capping layers.…”
Section: Differences In Between Dissimilar Materials Might Lead To DImentioning
confidence: 87%
“…It is worth noting that the migration energies of our capping layers are lower than that of LNO (Table I), [35,56,57,59,65] facilitating oxygen diffusion out of the LNO layer, resulting in oxygen deficiency in LNO. STO has the smallest migration energy, thus, it is not too surprising to see that the largest valence and lattice volume changes in LNO occur upon capping with STO (see Figure 1 and Figure 3).…”
Section: Differences In Between Dissimilar Materials Might Lead To DImentioning
confidence: 99%